Effects of Dietary Supplementation with High Fiber (Stevia Residue) on the Fecal Flora of Pregnant Sows - Yu, Miao (Animals (Basel), 2020)
SIMPLE SUMMARY: This study aimed to investigate the effects of different supplementation levels of stevia residues in high-fiber diets on the fecal microorganisms of pregnant sows. Stevia residue supplementation significantly increased the abundance of beneficial bacteria, such as g__Lachnospiraceae_XPB1014_group, g__Christensenellaceae_R-7_group, and g__Ruminococcaceae_UCG-005 (p < 0.05), and significantly reduced the abundance of harmful bacteria, such as Treponema_2 (p < 0.05), at the genus level. The stevia-residue supplementation reduced the feed cost, with the highest reduction rate being 13.33%. In conclusion, high-fiber diets can improve the intestinal balance and evenness index of the intestinal flora in pregnant sows, promote the relative abundance of beneficial bacteria, reduce the relative abundance of harmful bacteria, and reduce feed cost. ABSTRACT: This study aimed to investigate the effects of different supplementation levels of stevia residues in high-fiber diets on the fecal microorganisms of pregnant sows. Forty-eight first-farrowing Danish Landrace sows with similar weight, age, and due date were randomly divided into four groups. The control group was fed a normal diet (CON; 3.15% crude fiber content), and the treatment groups were supplemented with 20% stevia residue (SRL), 30% stevia residue (SRM), or 40% stevia residue (SRH) stevia residue, with crude fiber content of 7.79%, 9.15%, and 10.68%, respectively. The test period was 135 days, and Illumina Miseq high-throughput sequencing was used to test the fecal bacteria of the pregnant sows on day 56. Compared to the control group, species diversity was greater in the 30% stevia residue group. At the phylum level, Firmicutes and Spirochaetes had the greatest relative abundances; Firmicutes was most abundant in the SRM group, and Spirochaetes was most abundant in the CON group. At the genus level, Lactobacillus, Streptococcus, and Lachnospiraceae_XPB1014_group, and Treponema_2 had the highest relative abundances in the stevia-residue treatments. Among them, Lactobacillus and Treponema_2 were more abundant in SRL, Streptococcus was more abundant in SRH, and Lachnospiraceae_XPB1014_group was more abundant in SRM. Linear discriminant analysis effect size (LEfSe) showed that the bacterial species differed among the stevia residue treatments. SRL mainly included g__Lactobacillus and g__Romboutsi, SRM mainly included g__Lachnospiraceae_XPB1014_group and g__Ruminococcaceae_UCG_014, SRH mainly included g__Streptococcus, and CON mainly included g__Treponema_2, f__Clostridiaceae_1, g__norank_f__Muribaculaceae, and g__norank_f__p_251_o5. Stevia-residue supplementation significantly increased the abundance of beneficial bacteria, such as g__Lachnospiraceae_XPB1014_group, g__Christensenellaceae_R-7_group, and g__Ruminococcaceae_UCG-005 (p < 0.05), and significantly reduced the abundance of harmful bacteria, such as Treponema_2 (p < 0.05). Moreover, compared with the control group, the stevia-residues treatment groups reduced the feed cost 8.33%, 12.50%, and 13.33% per sow per day, respectively. In conclusion, high-fiber diets can improve the intestinal balance and evenness index of the intestinal flora in pregnant sows, promote the relative abundance of beneficial bacteria, reduce the relative abundance of harmful bacteria, and reduce feed cost. The optimal supplementation level of the stevia residue was found to be 30%.